Validation of the GRACE scores as a predictor of risk after acute myocardial infarction. - Maikel Santos Medina; Amauris Valera Sales; Yudelquis Ojeda Riquenes; Leticia Pardo Pérez1 (ECIMED, 2015)
Introduction: The GRACE score is now widely established as the best predictor of cardiovascular risk after acute myocardial infarction, however before use and apply validations are necessary to ensure that no erroneous probabilities. Objective: To validate GRACE score as a predictor of hospital mortality after suffering an acute myocardial infarction in the Cardiology Department of General Teaching Hospital "Dr. Ernesto Guevara" in the period from 2012 to 2013. Methodological design: A prospective study was carried out to validate the GRACE risk score as a predictor of hospital death in patients after acute myocardial infarction. The universe consisted of 310 patients in the first 24 hours of infarction in this period and the sample of 245 cases that could pick them study variables. Discrimination ability and the same calibration was used for validation of the scale, using statistical methods as the area under the curve and the Hosmer- Lemeshow respectively. Results: The average age was 65 + 12 and 68.9% were male. Hypertension was the most common factor associated. The 82.9% had ST segment elevation myocardial infarction and 19.5% had KK III-IV at admission. Most of the patients were classified as high risk. Mortality was 11%, all in high-risk patients being. The GRACE score had acceptable discrimination for hospital mortality with "c" of 0.771 and fit during calibration (p = 0.247 Conclusion: The GRACE scale had acceptable discrimination for hospital mortality. Key words: risk stratification, myocardial infarction, grace score.